Next-Generation Sequencing-Based Molecular Diagnosis of Choroideremia - Kayo Shimizu; Akio Oishi; Maho Oishi; Ken Ogino; Satoshi Morooka; Masako Sugahara; Norimoto Gotoh; Nagahisa Yoshimura (Case Reports in Ophthalmology, 2015)
We screened patients with choroideremia using next-generation sequencing (NGS) and identified a novel mutation and a known mutation in the CHM gene. One patient presented an atypical fundus appearance for choroideremia. Another patient presented macular hole retinal detachment in the left eye. The present case series shows the utility of NGS-based screening in patients with choroideremia. In addition, the presence of macular hole in 1 of the 2 patients, together with a previous report, indicated the susceptibility of patients with choroideremia to macular hole.